Teachers’ Strategies for Improving Students’ Reading Literacy at MIN 2 Kota Bengkulu (MODELING: Jurnal Program Studi PGMI, 2026)
Reading literacy is an important ability that supports students’ academic achievement and learning development. Teachers have an important role in developing students’ reading literacy through appropriate learning strategies and classroom activities. This study aims to analyze teachers’ strategies for improving students’ reading literacy at MIN 2 Kota Bengkulu. This study employed a qualitative approach with a descriptive research design. The data were collected through observations, interviews with teachers, and documentation of learning activities. The data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was examined through source and technique triangulation. The results show that teachers improve students’ reading literacy through several strategies, including guided reading activities, regular reading practice, the use of interesting reading materials, questioning and discussion activities, and individual assistance for students who experience reading difficulties. Teachers also provide motivation and create a supportive classroom environment to encourage students to read actively. The implementation of these strategies helps students improve their reading fluency, vocabulary, comprehension, and confidence in reading activities. The study concludes that teachers’ strategies play an important role in developing students’ reading literacy. Consistent implementation, appropriate learning materials, and cooperation between teachers, schools, and parents are needed to support the sustainable development of students’ reading literacy.